Pectin-based films and coatings with plant extracts as natural preservatives: A systematic review. (February 2022) - Nastasi, Joseph Robert; Kontogiorgos, Vassilis; Daygon, Venea Dara; Fitzgerald, Melissa A.
Abstract: Background: Pectin-based packaging containing plant extracts is a popular stream of derivative research of biopolymer-based food packaging. This packaging is unique because it is readily broken down into organic waste and easily infused with plant extracts to create active packaging with selective antimicrobial and antioxidant food preserving effects. Scope and approach: This review summarises current literature published on pectin-based packaging containing plant extracts and their application as a film or coating onto all types of food products to improve food shelf-life. This is achieved by systematically reviewing current literature and reporting the methods used to determine relevant research articles following the PRISMA guidelines. Key findings and conclusion: The major limitation of pectin-based packaging is its hydrophilic nature. Food with high surface moisture makes the application of this novel packaging material problematic for long-term storage. Research on the addition of hydrophobic plant extracts – such as essential oils and insoluble fibres – into pectin films or coatings has shown to improve hydrophobicity while still providing food preserving effects. Furthermore, combinations of these extracts can offer unique food preserving qualities and dual effects as plasticisers. Essential oils contain a plethora of bioactive compounds with selectivity for auto-oxidative and microbial pathways in food. Common essentials added to pectin films are those extracts from herbs and citrus because they contain compounds with strong antimicrobial properties. Pectin films have been applied to a range of foods with positive influences on shelf life, however, optimisation of the plant extract concentration and selection can be further employed to developed targeted food preservation systems. Highlights: Hydrophobic pectin-based packaging is viable for application on high moisture food. Plant extracts can offer dual activity as both antimicrobial and antioxidative agents. Plant extracts have selective roles against microbes as food preserving agents. Intelligent pectin-based food packaging can communicate shelf-life status to the user. Nanoemulsions of essential oils in pectin films/coatings improve compound stability.